The Role of the Insular Cortex and Serotonergic System in the Modulation of Long-Lasting Nociception - Ulises Coffeen; Gerardo B. Ramírez-Rodríguez; Karina Simón-Arceo; Francisco Mercado; Angélica Almanza; Orlando Jaimes; Doris Parra-Vitela; Mareli Vázquez-Barreto; Francisco Pellicer (Cells)
The insular cortex (IC) is a brain region that both receives relevant sensory information and is responsible for emotional and cognitive processes, allowing the perception of sensory information. The IC has connections with multiple sites of the pain matrix, including cortico-cortical interactions with the anterior cingulate cortex (ACC) and top-down connections with sites of descending pain inhibition. We explored the changes in the extracellular release of serotonin (5HT) and its major metabolite, 5-hydroxyindoleacetic acid (5HIAA), after inflammation was induced by carrageenan injection. Additionally, we explored the role of 5HT receptors (the 5HT1A, 5HT2A, and 5HT3 receptors) in the IC after inflammatory insult. The results showed an increase in the extracellular levels of 5HT and 5-HIAA during the inflammatory process compared to physiological levels. Additionally, the 5HT1A receptor was overexpressed. Finally, the 5HT1A, 5HT2A, and 5HT3 receptor blockade in the IC had antinociceptive effects. Our results highlight the role of serotonergic neurotransmission in long-lasting inflammatory nociception within the IC.